2006
DOI: 10.1021/jf0525176
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR, a Rapid Method to Monitor Organic Acids during Cupuassu (Theobroma grandiflorum Spreng) Processing

Abstract: The development of an analytical method using 1H nuclear magnetic resonance (1H NMR) spectrometry to monitor cupuassu (Theobroma grandiflorum Spreng) bean fermentation, drying, and roasting processes is reported. The analysis of organic acids and alcohols of crude water extracts of cupuassu ground kernels were monitored by HPLC and 1H NMR spectroscopy. The residual protein signals caused deleterious effects on acid and alcohol quantifications. Therefore, the analytical procedures were optimized by sample clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
(6 reference statements)
0
9
0
6
Order By: Relevance
“…Sample-to-sample variations caused by different genomic DNA recoveries and PCR amplification efficiencies were normalized on the basis of qPCR results using the primer set, Sketa2-F (5′-GGT TTC CGC AGC TGG G-3′)/Sketa2-R (5′-CCG AGC CGT CCT GGT CTA-3′), targeting the internal transcribed spacer region 2 of the rRNA gene operon in salmon testes DNA, as described previously [36]. The qPCR amplifications were conducted as described previously [25]. Two standard curves for the calculations of the bacterial and archaeal 16S rRNA gene copies were generated using pCR2.1 vectors (Invitrogen, USA) carrying bacterial ( Salimicrobium ) and archaeal ( Halarchaeum ) 16S rRNA genes derived from a saeu-jeot sample [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample-to-sample variations caused by different genomic DNA recoveries and PCR amplification efficiencies were normalized on the basis of qPCR results using the primer set, Sketa2-F (5′-GGT TTC CGC AGC TGG G-3′)/Sketa2-R (5′-CCG AGC CGT CCT GGT CTA-3′), targeting the internal transcribed spacer region 2 of the rRNA gene operon in salmon testes DNA, as described previously [36]. The qPCR amplifications were conducted as described previously [25]. Two standard curves for the calculations of the bacterial and archaeal 16S rRNA gene copies were generated using pCR2.1 vectors (Invitrogen, USA) carrying bacterial ( Salimicrobium ) and archaeal ( Halarchaeum ) 16S rRNA genes derived from a saeu-jeot sample [8].…”
Section: Methodsmentioning
confidence: 99%
“…Metabolite analysis using proton nuclear magnetic resonance ( 1 H NMR) spectroscopy is a comprehensive and easy technique for simultaneously monitoring diverse metabolites in fermented food processes [24]. A combination of pyrosequencing and 1 H NMR has been suggested to be one of the best ways to better understand the relationships between bacterial successions and metabolite changes during food fermentation [8], [25][29].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrosequencing of the 16S rRNA gene is a powerful approach to unravel complex microbial communities, including unculturable microbes, and proton nuclear magnetic resonance ( 1 H-NMR) is one of the most comprehensive and nondestructive methods for the simultaneous analysis of multiple compounds, especially in fermented foods [ 9 , 15 , 17 21 ]. Because fermentation of salted seafood usually occurs under high-salt conditions with approximately 25% (w/w) salts, Archaea may play an important role in salted seafood fermentation [ 22 ]; recently, however, the contribution of Archaea has been disputed [ 9 , 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification and quantification of the kimchi metabolites have been primarily achieved using traditional instruments such as high‐performance liquid chromatography (HPLC) and gas chromatography (GC) (Shim and others ), but it is almost impossible to analyze all kimchi metabolites simultaneously using the traditional instruments, especially over a long period of time because a wide variety of metabolites, having different chemical properties, are produced during kimchi fermentation. Proton nuclear magnetic resonance ( 1 H‐NMR) is one of the most powerful tools for simultaneously monitoring several metabolites present in 1 sample (Figueiredo and others ). Especially, it has been shown that a combination of 1 H‐NMR and multiplex barcoded pyrosequencing is a very comprehensive approach to understanding the relationships between the microbial community and metabolites in fermented food (Jung and others ; Jeong and others ).…”
Section: Introductionmentioning
confidence: 99%